The effects of fermented Astragalus polysaccharides on the growth performance, antioxidant capacity and intestinal health of broilers - Liu, Zhenkun; Zhang, Huaidan; Chen, Xianxin; Yu, Weiwei; Li, Shiyi; Kang, Lijuan; Li, Songlin; Jiang, Yilong; Zhou, Xinhong (Frontiers in Veterinary Science, 2025)
This study aimed to investigate the effects of fermented Astragalus polysaccharides(FAP) on the growth performance, antioxidant capacity and intestinal health of broilers. A total of 1,080 Cyan-shank Partridge chickens were divided into 4 groups, with 6 replicates per group and 45 chickens per replicate. Add 0% (T1), 0.2% (T5), 0.4% (T6) and 0.6% (T7) of FAP to the basal diet, respectively. The trial lasted for 42 days. The results indicated that, compared to the T1 group, FW and ADG of broilers in each treatment group were significantly increased (p < 0.05). The slaughter rates of the T6 and T7 groups were significantly higher compared to the T1 group, meanwhile, the carcass yields of the T5, T6, and T7 groups were notably enhanced (p < 0.05). Compared with T1 group, the activities of CAT, GSH-Px and the content of T-AOC in T6 and T7 groups were increased (p < 0.05), while the content of MDA was decreased (p < 0.05). All groups exhibited significantly VH and VH/CD in the duodenum compared to the T1 group (p < 0.05). Compared with the T1 group, the relative mRNA expression levels of ZO-1 and Claudin in the jejunal mucosa of broilers in all groups were significantly up-regulated, while the expressions of IL-1β, IL-6, TNF-α, and IFN-γ were down-regulated (p < 0.05). 16S rDNA sequencing analysis revealed that at the phylum level, the abundance of Verrucomicrobiota in the T6 group was significantly increased compared to the T1 group (p < 0.05). Cyanobacteria, Nitrospirota, Elusimicrobiota, and Acidobacteriota were unique to the T6 group, while Cyanobacteria and Elusimicrobiota were unique to the T5 group compared to the T1 group. At the genus level, the abundance of Desulfovibrio was significantly reduced in the T6 group compared to the T1 group (p < 0.05). Additionally, fermented Astragalus polysaccharides increased the abundance of Bacteroidota, Campilobacterota, Deferribacterota, Firmicutes, Fusobacteriota, Proteobacteria, and Spirochaetota (p < 0.05). The LEfSe analysis found that Clostridia_vadinBB60_group and Comamonas were identified as potential biomarkers. Overall, feeding fermented Astragalus polysaccharides can enhance the growth performance, slaughter characteristics, and antioxidant capacity of broiler chickens by modulating the gut microbiota and strengthening intestinal barrier function.